2015
DOI: 10.1080/00036846.2015.1105926
|View full text |Cite
|
Sign up to set email alerts
|

Would information on consumer confidence have helped to predict UK household expenditure during the recent economic crisis?

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The results on the predictability of consumer attitudes toward consumer spending are somewhat mixed. The effect of consumer sentiment on consumption has been analyzed by, among others Carroll et al (1994), Kwan and Cotsomitis (2004), Ludvigson (2004), Easaw et al (2005), Kwan and Cotsomitis (2006), Malgarini and Margani (2007), Celik and Ozerkek (2009), Bruno (2014), Kilic and Cankaya (2016), Gausden and Hasan (2016), Lahiri et al (2016), Juhro and Iyke (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results on the predictability of consumer attitudes toward consumer spending are somewhat mixed. The effect of consumer sentiment on consumption has been analyzed by, among others Carroll et al (1994), Kwan and Cotsomitis (2004), Ludvigson (2004), Easaw et al (2005), Kwan and Cotsomitis (2006), Malgarini and Margani (2007), Celik and Ozerkek (2009), Bruno (2014), Kilic and Cankaya (2016), Gausden and Hasan (2016), Lahiri et al (2016), Juhro and Iyke (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study departs from this extant work by positing a pivotal (i) direct and/or (ii) intermediary role for subjective individual perception of economic circumstances and sentiment surrounding macroeconomic performance, sometimes also described as 'consumer confidence'. Given the prevalence of this concept in theoretical and empirical analyses in economics (see, for example, Ludvigson, 2004;Barsky et al, 2012;Gausden and Hasan, 2016), finance (see, for example, Fisher and Statman, 2003;Lemmon & Portniaguina, 2006), and psychology (see, for example, Spreng & Page, 2001;Chelminski & Coulter, 2007;Bovi, 2009) it is somewhat surprising that its potential role in exploring variations in suicide rates has not, hitherto, been explicitly explored. If such an intermediary role could be empirically identified, it may well serve as a suitable candidate metric for a Durkheimian transmission mechanism by which actual economic circumstances or crises affect suicide rates.…”
Section: Theoretical Considerations and Key Hypothesesmentioning
confidence: 99%
“…In a recent paper, Gausden and Hasan (2016) proposed a minor modification to the CCI. Reasons were supplied for seeking to deny Q11 a contribution towards the creation of an aggregate measure of consumer sentiment.…”
Section: Question 11mentioning
confidence: 99%
“…Inter alia, both Gausden and Hasan (2016) and Lahiri, Monokroussos and Zhao (2016) have identified that information on consumer confidence serves a more productive role in forecasting household spending during an economic downturn. On this basis, perhaps it should not be surprising to find that the data on Italy, compared to those on Germany and the UK, allow a clearer distinction to be drawn between the predictive capabilities of the rival models.…”
Section: Table 2dmentioning
confidence: 99%
See 1 more Smart Citation